Mobilisasi Aksi Protes Massal Melalui Fitur Template di Instagram - Kahar, Sharlah Aulia (Emik, 2025)
Social media as a sophisticated technology presented by humans has become a medium for mobilizing mass protests, especially Instagram in this modern era. One of the features on Instagram, namely the template feature, has become a new medium for carrying out mass protests. In this article, we will discuss how the template feature becomes a medium for mobilizing spontaneous mass protests on Instagram which becomes a space for public participation in determining the direction of policy which in this case is interpreted as cyberdemocracy. This qualitative research was conducted using a netnographic approach. Netnographic research is used to explore culture in digital space, especially how people utilize digital space in activism movements through the template feature on Instagram. This study involved twelve informants aged (between 21 and 32 years) and acted as template makers and template distributors. Data collection in this study used observation and in-depth interview methods that lasted for six months. Mass protests through the template feature on Instagram discussed various issues ranging from problems related to sexual violence, government policies, human rights violations, and various other issues that are currently occurring in society. This action occurred due to the limitations of real space in voicing public aspirations and driven by the tendency to follow trends (virality). This template feature is used as a mobilization medium because the use of features that are more practical and easy to disseminate. In addition, the public can more easily accept the information conveyed through this template feature because of the presentation of the protest narrative which is made concisely. By utilizing this feature as a medium for mass protest actions on Instagram, it becomes a space for conveying public opinion in an effort to intervene in public policy.